Tindak Tutur Asertif Dalam Podcast Bersama Sherly Annavita Pada Kanal Youtube Inilahcom - Nailul Muthoharoh; Asropah Asropah; Nanik Setyawati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to describe assertive illocutionary speech acts in podcasts with Sherly Annavita on the YouTube channel inicom. The data collection methods and techniques used in this research are the listening method and the skillful free-involved listening technique. The data analysis methods and techniques used in this research are the matching method and the technique of selecting determining elements. The presentation of the analysis results in this research uses informal techniques. The results of this research show that the most dominant type of assertive speech act is speech stating a number of 10 data; Next, the speech explaining, the speech informing, and the speech giving an opinion each contain 6 data.